Mine dumps, wheeze, asthma, and rhinoconjunctivitis among adolescents in South Africa: any association? - Nkosi, Vusumuzi (Int J Environ Health Res, 2015)
The study investigated the association between community proximity to mine dumps, and current wheeze, rhinoconjunctivitis, and asthma among adolescents. This study was conducted during May–November 2012 around five mine dumps in South Africa. Communities in close proximity to mine dumps had an increased likelihood of current wheeze OR 1.38 (95 % CI: 1.10–1.71), rhinoconjunctivitis OR 1.54 (95 % CI: 1.29–1.82), and a protective association with asthma OR 0.29 (95 % CI: 0.23–0.35). Factors associated with health outcomes included other indoor and outdoor pollution sources. Wheeze and rhinoconjunctivitis appear to be a public health problem in these communities. The findings of this study serve as a base for further detailed epidemiological studies for communities in close proximity to the mine dumps e.g. a planned birth cohort study.